3 - L’intégration économique de l’Afrique de l’Ouest confrontée aux solides liens de dépendance des états africains de l’extérieur - FALL, Ely (Africa Development, 1984)
With the establishment of the Economic Community of West African States (ECOWAS) in Lagos, in 1975, the West African States were pla- cing their high hopes for development on economic integration. Such an integration implies however, both a development of inter- state economic relations and a slackening of relationships with non-Community states. These two types of relationships are opposed. But, as it happens, the second type of relationships with non-Community states, that is, North- South economic relations or vertical relations is more firmly established and more powerful. Foreign public investments throw light upon these vertical links. These investments in the form of assistance, loans and grants of all sorts are what developed countries and multi-lateral public agencies supply Third World countries with. Assistance is granted in many forms: either donations, in the forms of financial contributions or public interest works: building of schools or hospitals, etc. or bi-lateral or multi-lateral aid. Besides aid, bi- lateral loans are made with favorable terms. Foreign public investments of all sorts have been made in ECO- WAS states. These investments are tied however. They usually channel benefi- ciary countries economies towards international specializations which consolidate their dependence on the outside world. Therefore, they impede states regional economic integration, an event which should reduce depen- dence on the outside world as it brings the complementarity of African states into play and therefore strengthens their horizontal or South-South relations. The amounts invested in the past decade in West Africa show that the increase of aid, under such conditions, does not necessarily promote the development of these states. Indeed, a contrast appears between the amounts invested and the poor progress in the economic development of these countries. Ely FALL, Maître Assistant à la Faculté des Sciences Juridiques et Economiques de l'Université de Dakar